Avalia????o de blocos intertravados manufaturados com concreto dosado com res??duos de PET como alternativa sustent??vel na constru????o civil - Pires, Giselle Waldtraut Mathes Orcioli (2015)
The construction sector is responsible for consuming a large portion of non-renewable natural resources and generate significant environmental impacts, showing the need for actions that enable new constructive practical alternatives to mitigate damage to the environment caused by this sector. Faced with this panorama, technological innovation is necessary to achieve the intended objectives, the study of new technologies using the most different segments of industry waste and reinserting them into new products, and meet the need of environmental management mitigating the impacts generated It contributes to the development of a sustainable building segment. This time, this work aimed to propose an alternative material in the form of a concrete block interlocked floor, manufactured with part of their natural aggregates replaced by PET waste. To use this material in construction is necessary to meet the technical parameters required by NBR 9781: 2013 "Concrete paving pices". Among the parameters required is the block characteristic resistance, which must be greater than or equal to 35 MPa. To obtain this, studies of dosage were conducted contemplating the running 14 concrete mixtures divided into two groups, in which one was compound without PET waste and the other group containing PET waste, which have replaced part of the natural aggregate in percentages ranging between 10% and 60%. The concrete block with PET waste reached to 40,5 MPa with 33,8% of PET content demonstrating its technical feasibility. Following was carried out a comparison between the estimates of production costs between conventional material and with PET, which proved more costly for regions with abundant natural aggregates, however became alternative in places where there is a shortage of these materials. Finally, it was shown that the use of concrete with PET could fail to consume the total of 608 kg of natural aggregates per cubic meter of concrete and have recycled 72.2 kg of PET waste or 1,588 PET bottles per cubic meter of concrete. This exchange of materials allowed assist in the mitigation of environmental impacts caused by the construction and suggested a new alternative recycling of PET waste.